2008
DOI: 10.1007/s00167-008-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Participation in sporting activities following knee replacement: total versus unicompartmental

Abstract: Few studies have been published assessing patients sporting activity after total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA). Common concerns of patients undergoing TKA or UKA are whether they can continue with sporting activities after surgery. This study compares the sporting activity of TKA and UKA patients preoperatively and postoperatively. A total of 110 patients were surveyed by questionnaire. Seventy-six patients had undergone TKA and 34 patients had undergone UKA. They were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
4
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(159 citation statements)
references
References 12 publications
5
140
4
10
Order By: Relevance
“…This study reveals satisfaction is similar amongst postoperative UKR and TKR groups when matched for age. In keeping with published literature [6,14], this study found that a UKR procedure confers better functional outcome in terms of recreation and sport compared to TKR procedures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study reveals satisfaction is similar amongst postoperative UKR and TKR groups when matched for age. In keeping with published literature [6,14], this study found that a UKR procedure confers better functional outcome in terms of recreation and sport compared to TKR procedures.…”
Section: Discussionsupporting
confidence: 87%
“…While TKR and UKR have been performed in many patients, with proven efficacy and durability, some surgeons prefer the longer track record of TKR, while others prefer the benefits afforded by UKR including restoration of more normal joint kinematics, better range of movement and faster recovery compared to TKR, resulting in lower morbidity and higher cost-effectiveness [1,5,10,11]. It has also been shown that patients undergoing UKR are more likely to return to sporting activities postoperatively than following a TKR [6]. Some studies show low patient satisfaction with UKR in younger cohorts [13]; however, studies of joint registry and nationally collated patient-reported outcome measures data show UKR patients typically undergo revision with a higher satisfaction level compared to TKR patients [3,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hopper et al found a high "return-to-sport-rate" after UKA of 97 % in their patients [8]. However, the average patient age of 63 years in their study was younger.…”
Section: Discussionmentioning
confidence: 69%
“…Advantages of a UKA include lower postoperative morbidity, quicker return to activities, and more normal feeling of the knee in comparison to the advantages after a TKA [1,8,9], and some single-center studies report UKA results that are comparable to those of TKAs [12,13,15,18,22]. However, these studies are not supported by available implant register data from Finland, Norway, Sweden, Australia, New Zealand, and the United Kingdom [10,[23][24][25][26][27], which repeatedly report inferior midterm survivorship of UKAs compared with TKAs.…”
Section: Introductionmentioning
confidence: 99%